Regulators of Tfh Cell Differentiation - Jogdand, Gajendra M.; Mohanty, Suchitra; Devadas, Satish (Frontiers in Immunology, 2016)
The follicular helper T (Tfh) cells help is critical for activation of B cells, antibody class switching and germinal center formation. The Tfh cells are characterized by the expression of CXCR5, ICOS, PD-1, Bcl-6, and IL-21. They are involved in clearing infections and are adversely linked with autoimmune diseases and also have a role in viral replication as well as clearance. Tfh cells are generated from naïve CD4 T cells with sequential steps involving cytokine signaling (IL-21, IL-6, IL-12, activin A), migration and positioning in the germinal center by CXCR5, surface receptors (ICOS/ICOSL, SAP/SLAM) as well as transcription factor (Bcl-6, c-Maf, STAT3) signaling and repressor miR155. On the other hand Tfh generation is negatively regulated at specific steps of Tfh generation by specific cytokine (IL-2, IL-7), surface receptor (PD-1, CTLA-4), transcription factors Blimp-1, STAT5, T-bet, KLF-2 signaling and repressor miR 146a. Interestingly, miR 17-92 and FOXO1 acts as a positive as well as a negative regulator of Tfh differentiation depending on the time of expression and disease specificity. Tfh cells are also generated from the conversion of other effector T cells as exemplified by Th1 cells converting into Tfh during viral infection. The mechanistic details of effector T cells conversion into Tfh are yet to be clear. To manipulate Tfh cells for therapeutic implication and or for effective vaccination strategies, it is important to know positive and negative regulators of Tfh generation. Hence, in this review we have highlighted and interlinked molecular signaling from cytokines, surface receptors, transcription factors, ubiquitin Ligase and miRNA as positive and negative regulators for Tfh differentiation.